Preparation and Characterization of Perfluorosulfonate‐Free Phosphosilicate Glass‐Based Composite Proton‐Exchange Membrane. Issue 2 (1st February 2013) - Di, Z.; Li, H.; Li, M.; Mao, D.; Chen, X.; Xiao, M.
Abstract Based on hydrothermally treated phosphosilicate (SiO2–P2O5) glass and sulfonated poly(ether ether ketone) (SPEEK) polymer, perfluorosulfonate‐free SiO2–P2O5/SPEEK composite membranes are prepared. The morphology, thermal and mechanical properties, pore structure, proton conductivity, water uptake, as well as the fuel cell performances of the SiO2–P2O5/SPEEK composite membranes are investigated. The SiO2–P2O5/SPEEK composite membranes with proton conductive SiO2–P2O5 glass powders of more than 50 wt.% were determined to be flexible due to the incorporation of the SPEEK polymer component, and it showed proton conductivities of above 10–2 S cm–1. A single H2/O2 fuel cell was assembled based on the SiO2–P2O5/SPEEK composite membrane, and was found to release a peak power density of 355.6 mW cm–2 at 68 °C.